123k views
4 votes
HELPPPPPPPPPPPPPP 100 POINTS IF YOU ANSWER ALL CORRECT

HELPPPPPPPPPPPPPP 100 POINTS IF YOU ANSWER ALL CORRECT-example-1
User Jeff Bezos
by
6.2k points

1 Answer

6 votes

Answer:


\left[\begin{array}{ccc}y=x&y=(2)/(3)x&y=(2)/(3)x +1 \\-6&-4&-3\\-3&-2&-1\\0&0&1\\3&2&3\\6&4&5\end{array}\right]

Explanation:

-6: y = -6

y =
(2)/(3) (-6)

y = -4

y =
(2)/(3) (-6) + 1

y = -4 + 1

y = -3

-3: y = -3

y =
(2)/(3) (-3)

y = -2

y =
(2)/(3) (-3) + 1

y = -2 + 1

y = -1

0: y = 0

y =
(2)/(3) (0)

y = 0

y =
(2)/(3) (0) + 1

y = 1

3: y = 3

y =
(2)/(3) (3)

y = 2

y =
(2)/(3) (3) + 1

y = 2 + 1

y = 3

6: y = 6

y =
(2)/(3) (6)

y = 4

y =
(2)/(3) (6) + 1

y = 4 + 1

y = 5

User Krishanu Dey
by
5.4k points